Pulsion severity showed a good correlation with cognitive function in Parkinson's disease. (November 2014) - Kurata, Tomoko; Hatanaka, Noriko; Morimoto, Nobutoshi; Deguchi, Shoko; Deguchi, Kentaro; Ikeda, Yoshio; Abe, Koji
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: To examine the correlation between cognitive impairment and postural instability in Parkinson's disease (PD) patients by using posturography. Methods: We investigated 88 PD patients comparing clinical scorings of cognitive functions and pulsion severity, and quantitative measurement of postural instability by posturography with the length of the center of gravity (LNG) and envelope area (ENV). Results: The number of patients with severe pulsion increased in PD with disease progression assessed by Hoehn and Yahr (H & Y) scale regardless of age, and a significant correlation was observed between the pulsion severity and both LNG (R = 0·4242) and ENV (R = 0·4335). Both LNG and ENV showed a good correlation with all cognitive assessments such as mini-mental state examination (MMSE), Montreal cognitive assessment (MoCA), and frontal assessment battery (FAB), suggesting that cognitive impairment became worse with the longer LNG and the larger ENV. Among the cognitive assessments, MoCA showed the highest correlation (R = 0·56–0·62) with both LNG and ENV, reflecting that MoCA is the most sensitive and reliable screening for dementia in PD. Discussion: The present study showed that posturography is useful to quantify the pulsion severity in PD patients, that pulsion severity and cognitive function showed a good correlation especially assessed by MoCA, and that posturography thus provides a more detailed quantitative correlation of postural instability to cognitive impairment.